Sustainable cities: enhancing food systems with urban agriculture - Zafar Tabrez (Discover Food)
Abstract Urban agriculture promotes urban sustainability through its contributions to food production, income generation, trash recycling, prevention of urban sprawl, preservation of biodiversity, and enhancement of resilience and local economies. Various types of urban agriculture are essential for improving food security viz., achieving a sustainable implementation requires integrating urban farming into urban planning processes. There is a clear requirement for policies specifically tailored to tackle the issues related to urban agriculture. Incorporating urban gardening into urban planning processes and bolstering it with policies enhances its sustainability. Urban planning must include urban farming for sustainability and food security and to raise awareness, reduce poverty, and improve food systems. Safe urban farming spaces reduce risks in vulnerable areas. Urban gardens mitigate urban heat islands, waste, and air pollution, improve physical and mental health, and foster social connections. Organic agriculture boosts biodiversity, while urban food production reduces transportation, storage, and packaging CO2 emissions, fighting climate change.